Exploring the effects of olfactory VR on visuospatial memory and cognitive processing in older adults - Ryota Sunami; Takamichi Nakamoto; Nathan Cohen; Takefumi Kobayashi; Kohsuke Yamamoto (Scientific Reports)
Abstract This study examined the effects of Olfactory Virtual Reality (VR) Gaming on cognitive performance in older adults. A VR game environment (“Interactive Smellscape”) was created to enable this, and 30 participants aged 63–90 years completed both VR gaming sessions and cognitive assessments, conducted with a 6-day interval between the two sessions. Significant improvements were observed in spatial tasks of Japanese characters and words, with notable enhancements specifically in visuospatial rotation performance and word-location recall accuracy. However, no significant changes were detected in olfactory identification or other general cognitive tasks. These findings suggest potential cognitive benefits of incorporating VR and olfactory stimuli into interventions for older populations, particularly for tasks requiring attention and spatial processing. The results further underscore the importance of task-specific designs to maximize the utility of multisensory VR systems for cognitive rehabilitation.